Spinal Schwannoma; Analysis of 40 Cases - Jee Ho Jeon; Hyung Sik Hwang; Je Hoon Jeong; Se Hyuk Park; Jae Gon Moon; Chang Hyun Kim (2008)
This study is to report our experience of 40 cases of spinal schwannoma.From 1995 to 2006, medical records were retrospectively reviewed in 40 cases of spinal schwannoma.We treated 40 spinal schwannomas in 38 (22 male and 16 female) patients. The mean age was 50.2. Four cases were sited in the cervical spine, 11 cases in the thoracic spine, and 25 cases in the lumbar spine. Two patients showed recurrences. Thirty-eight cases were intradural-extramedullary type and 2 cases were extradural. Two cases (5%) including 1 recurred case had no postoperative motor improvement. Ninety-five percents of patients improved on postoperative motor grade.Spinal schwannoma is mostly benign and extramedullary tumor. There were 2 recurred cases (5%) that had history of previous subtotal removal at first operation and had shown worse prognosis compared with the cases without recurrence. To reduce the recurrence of spinal schannoma, total excision of tumor mass should be done.